Association of Admission Glycaemia and 2 Year All-cause Mortality Risk in Diabetic Patients with Acute Coronary Events in Ban Mi Hospital - Suttiwong, Nisarat (Journal of Health Science of Thailand, 2017)
A retrospective cohort study was carried out by collecting data from medical records of diabetes mellitus and unstable angina or non Q-wave myocardial infarct patients who were admitted to Ban Mi hospital during January 2004 - March 2007. A total of 141 consecutive patients with diabeteswere included. The primary study end point was 2 year all- cause mortality collected from website of National Health Security Office www.nhso.go.th. During the 2 year follow up 38 patients (26.9%) died. Patients were stratified into quartile groups defined by admission capillary glucose according to percentile 25, 50 and 75 ranks. In univariate analyses, higher blood glucose levels at admission were associated with increase duration of diabetes, more congestive heart failure at admission and the level of blood glucose was inversely associated with the use of lipid-lowering drugs. Increased admission blood glucose across quartiles was associated with increasing mortality at 2 years. Using the lowest glucose quartile as a reference, the adjusted 2 year mortality risk was found to be significantly higher in the highest glucose quartiles HR 41.49 (1.42-1209.69, p=0.030).